2015
DOI: 10.1590/s0102-865020150080000001
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible folic acid reduce anorectal malformations ethylenethiourea induced in rats?

Abstract: PURPOSE:To investigate the effect of folic acid (FA) in an experimental model of anorectal malformations (ARMs) ethylenethiourea (ETU) induced. METHODS:Eight female Wistar rats were divided randomly in two groups. Group A -ETU; Group B -FA+ETU; Dams from group B received daily, since two weeks before pregnancy to the end of pregnancy, FA (50mg/kg) by gavage. Dams from groups A and B, received 1% ETU (125mk/kg) by gavage on gestational day (GD) 11. Their fetuses were harvested by cesarean section on GD21 and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Our meta-analysis, however, could not show any association with ARM. In contrast, the study by Faria et al [ 88 ] observed in their experimental model a reducing effect in the incidence of ARM when inducing ethylenethiourea in rats.…”
Section: Discussionmentioning
confidence: 74%
“…Our meta-analysis, however, could not show any association with ARM. In contrast, the study by Faria et al [ 88 ] observed in their experimental model a reducing effect in the incidence of ARM when inducing ethylenethiourea in rats.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, coadministration of both drugs significantly minimized similarly the hazards of AZA on the fetal development. At the same direction, folic acid reduces the incidence of anorectal malformations induced by ethylenethiourea in rats (Faria et al, 2015). Micronutrients like folic acid and vitamin B12 are important determinants of the one carbon cycle and play a critical role in determining pregnancy outcome (Gadgil et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion of the study was that the FA (received daily, for 2 weeks before pregnancy until the end of pregnancy) reduces the incidence of ARM induced by ETU in rats. 32 Using a modified experimental model of ARM (adriamycin induced in rats), the effect of FA to prevent the induction of ARM was studied. 33 The results demonstrate that the use of FA reduces the numbers of ARM and enlarged the thickness of intestinal epithelium when compared with the controls.…”
Section: Introductionmentioning
confidence: 99%